The Absent Academy: the Organisation of Classical Scholarship in Nineteenth-century England - Stray, Christopher (Hyperboreus, 2014)
The focus of the paper is on the surprisingly late creation of the British Academy (1902). It is shown how, in the absence of an Academy, Classical studies were organized in nineteenth-century Great Britain: the peculiarities and correlations of the Universities, the emergence of Classical journals, and the possibilities of building a scholarly career.